TATA KELOLA REKAM MEDIS ELEKTRONIK BERBASIS TEKNOLOGI INFORMASI DALAM PELAPORAN PASIEN IGD DENGAN METODE AGILE - Nabila, Silvy; Widyani, Pipih; Syahidin, Yuda; Yunengsih, Yuyun (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
This system functions to record daily, monthly, and yearly censuses without changing the performance of the computer used because the data is stored using cloud storage. The purpose of this study was to determine the governance of information technology-based electronic medical records in reporting emergency department patients using the Agile method. The recording of daily, monthly, and yearly censuses in the emergency room at Hermina Arcamanik Hospital in Bandung is not optimal due to frequent problems with the local area network (LAN); computers often hang or freeze, and the system has not been updated. Currently, the recording of daily, monthly, and yearly sensors still uses the Visual Basic program, which has the concern that it requires a very large amount of memory during the installation process. Management of information technology-based electronic medical records in reporting emergency department patients using agile methods The agile method used in the development of this program is feature-driven development (FDD). The system that has been made is tested using the black-box testing method. This program only focuses on completing a certain program and produces medical record management for reporting emergency department patients based on information technology in order to speed up the work process and minimize the occurrence of device errors.